1992
DOI: 10.1002/bies.950141208
|View full text |Cite
|
Sign up to set email alerts
|

Mouse albino‐deletions: From genetics to genes in development

Abstract: Six essential genes located near the mouse albino locus have been identified as required during specific periods of development, Amongst these six, each is required either during the preimplantation stages of development, at specific times during gastrulation, within 12 hrs after birth or during juvenile development. These genes were identified as a result of extensive genetic complementation analysis using embryos homozygous for the albino deletions. Although, in principal, the associated developmental abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 61 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…Approximately 12 loci or genes have been identified, which are required for normal development during gas trulation and before somite formation (E6-E8) (Green 1989;Holdener-Kenny et al 1992). Of these, the pheno type of the recessive lethal mutation t"^^ is most similar to that of HNF-4 homozygotes; t"^^ is one of several em bryonic lethals found in different t haplotypes of the t complex on chromosome 17 (Bennett 1975;Silver 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 12 loci or genes have been identified, which are required for normal development during gas trulation and before somite formation (E6-E8) (Green 1989;Holdener-Kenny et al 1992). Of these, the pheno type of the recessive lethal mutation t"^^ is most similar to that of HNF-4 homozygotes; t"^^ is one of several em bryonic lethals found in different t haplotypes of the t complex on chromosome 17 (Bennett 1975;Silver 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the T gene product seems to be required to ensure correct formation and/or specification of the mesodermal lineage. Although classical genetic studies have identified a number of spontaneous mutations that similarly interfere with early embryogenesis, the underlying defects have yet to be elucidated at the molecular level (reviewed by Lyon and Searle, 1989;Holdener-Kenny et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the albino deletion complex on chromosome 7 is perhaps the best characterized phenotypically and molecularly (Rinchik and Russell 1990;Holdener-Kenny et al 1992). Many of the albino deletions cause recessive lethal phenotypes, such as arrest of development at specific embryological stages or failure to survive beyond birth (Erickson et al 1968;Russell et al 1979).…”
mentioning
confidence: 99%